Direct Numerical Simulation of Heat Transfer of Lead–Bismuth Eutectic Flow Over a Circular Cylinder at Re = 500 - Chen, Li-Xia; Yuan, Chao; Zhao, Jun-Long; Zhang, Hong-Na; Ma, Yu; Li, Feng-Chen (Frontiers in Energy Research, 2022)
The flow and heat transfer characteristics of the lead–bismuth eutectic (LBE) (Prandtl number Pr = 0.025) passing over a circular cylinder at Re = 500 are studied by direct numerical simulation and compared with the case of the air (Pr = 0.71). This article makes two major contributions: (1) heat transfer characteristics for the LBE flowing past a circular cylinder. For the case of air, the results show that a similarity exists among the wake structure of instantaneous temperature, fluctuating temperature, and velocity. However, these fields differ severely for the case of LBE. The local time-averaged Nusselt number (Nu¯) and circumferentially averaged Nu¯ are smaller in the LBE than that in the air. The circumferential and spanwise distributions of Nu¯ in the LBE show a greater uniformity. The regions with larger circumferential or spanwise inhomogeneity appear in the flow separation zone. Besides, a resemblance between the distribution of the root mean square of fluctuation temperature and the turbulence kinetic energy can be recognized in the air; however, the similarity disappears for the case of LBE and in which the temperature fluctuation is smaller than that in the air. (2) Study on the temperature and velocity defect laws in the wake. By introducing the defect scales, it is concluded that the velocity field has not entered the self-preserving state yet, while the self-preserving state starts at the location of five times the diameter of the cylinder downstream of the cylinder for the temperature in the LBE and that of 21 times for the temperature in the air. In summary, even if without taking the buoyancy force into consideration, this article provides a fruitful description of the flow and heat transfer characteristics when the LBE flows past a cylinder, which is a typical flow in a helical coil steam generator of lead–bismuth alloy-cooled fast reactors. These highly resolved data on velocity and temperature are valuable for turbulence and heat fluxes modeling in the future and may facilitate the in-depth understanding of such flow and heat transfer characteristics within a limited variation range of operating temperature.